PROBLEMATIKA PRAKTIK PEMBERIAN KETERANGAN AHLI HUKUM PIDANA DALAM PEMBUKTIAN TINDAK PIDANA KORUPSI - Effendi, Erdianto (LITIGASI, 2023)
Expert testimony is one of the pieces of evidence used in criminal procedural law based on the provisions of Article 184 of the Criminal Procedure Code. The testimony of criminal law experts is also used in proving corruption crimes. In practice, there are several problems related to the role of criminal law experts in proving corruption. Among the issues are allegations of non-objectiveness of experts in providing information. The information provided tends to benefit one presents it. This research uses a normative approach. The results of the study empirically found several problems in the evidentiary process using the testimony of criminal law experts. Some of these problems include: What should a criminal law expert prove, who should present an expert, whether investigators and judges are bound with the testimony of criminal law experts, whether the experts testimony is based on operational costs and honorariums, and other questions to which juridically answers have not been found.. Based on these findings, it is hoped that there wil.l be clear arrangements regarding the role of criminal law experts in proving corruption crimes. Keywords: Criminal Law Expert, Proof, Crime of Corruption.